Trifecta Outcomes in Open, Laparoscopy or Robotic Partial Nephrectomy: Does the Surgical Approach Matter? (Journal of Kidney Cancer, 2019)
This retrospective study evaluated perioperative outcomes of open partial nephrectomy (OPN), laparoscopic partial nephrectomy (LPN), and robot-assisted partial nephrectomy (RAPN) and identified predictive factors of Trifecta achievement for renal tumors that underwent partial nephrectomy (PN) in a single institutional cohort. The study involved patients who underwent PN from January 2011 to July 2018. Trifecta was defined as absence of perioperative complications, no positive surgical margins, and ischemia time